2012
DOI: 10.1002/asi.22694
|View full text |Cite
|
Sign up to set email alerts
|

PubMed searches by Dutch‐speaking nursing students: The impact of language and system experience

Abstract: This study analyzes the search behavior of Dutch‐speaking nursing students with a nonnative knowledge of English who searched for information in MEDLINE/PubMed about a specific theme in nursing. We examine whether and to what extent their search efficiency is affected by their language skills. Our task‐oriented approach focuses on three stages of the information retrieval process: need articulation, query formulation, and relevance judgment. The test participants completed a pretest questionnaire, which gave u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This corroborates our previous finding that the extra step of selecting MeSH terms can be very useful to prevent errors from percolating to the final query (Vanopstal, et al, 2012).…”
Section: Query Reformulationsupporting
confidence: 80%
See 4 more Smart Citations
“…This corroborates our previous finding that the extra step of selecting MeSH terms can be very useful to prevent errors from percolating to the final query (Vanopstal, et al, 2012).…”
Section: Query Reformulationsupporting
confidence: 80%
“…the time spent on searching for MeSH terms and combining them into a query. As we explained in our previous study (Vanopstal, et al, 2012), longer querying times can indicate hesitation. A one-way ANOVA test showed that there were significant differences in querying times between the performer types (F(2, 95)= 11.896, p<.001).…”
Section: Search Processmentioning
confidence: 99%
See 3 more Smart Citations